Development and performance evaluation of plantain peeler cum slicer - ASWATHI K. B INDULEKSHMI; Er. Rajesh G. K (Guide) (Tavanur 2010 Kelappaji College of Agricultural Engineering and Technnology)
Development and performance evaluation of plantain peeler cum slicer
Development and performance evaluation of plantain peeler cum slicer